Czy Europa umiera - nasz głos w dyskusji - Tomaszyk, Mikołaj; Raubo, Jacek (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
The authors of the article discuss selected shortcomings of European integration, concentrating on such problems as a future vision of Europe, its position in international and global relations, as well as the process of building common security structures. The article is based on the assumption that Europe needs to rethink and openly analyze its problems that have arisen in the 21st century